Meta-Analisis Implementasi Landasan Ilmu Pendidikan terhadap Pengembangan Bahan Ajar dalam Pembelajaran Fisika pada Era Revolusi Industri 4.0 - Cahyati, Mona Trisna; Usman, Esti Aprilia; Putri, Yosa Aulya (Universitas Negeri Padang, 2019)
The foundation of education greatly contributes to learning, especially in achieving the learning objectives to be achieved. Based on the needs of students using teaching resources, then a meta-analysis of the implementation of educational science foundation on the development of teaching materials in learning physics in the era of the industrial revolution 4.0. This meta analysis uses descriptive methods. The purpose of this analysis meta to observe the educational foundation that has been found in selected journals as many as 20 journals. The data in this study were obtained from the analysis of each journal and strengthened by existing theories. The data analysis technique uses descriptive percentages. The results of the meta-analysis are as follows. Application of religious foundation with a percentage of 10% (not good), constitutional basis 50% (less), philosophical foundation 5% (not good), psychological foundation 50% (not good), social foundation 25% (not good), cultural and anthropological 20% (not good), and 80% of science and technology application (enough). Based on the results of the study it can be concluded that the application of educational science foundation in the development of teaching materials is still in the bad category.